Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1080/13557858.2016.1246938
|View full text |Cite
|
Sign up to set email alerts
|

Communication about sex and HPV among Puerto Rican mothers and daughters

Abstract: Objective Although opportunities to vaccinate against human papillomavirus (HPV), are available, vaccination rates in Puerto Rico remain low. Communication between parents and adolescents about sexual topics may influence decisions about HPV vaccination uptake, particularly among young women; yet few studies have addressed this issue. This qualitative study explored Puerto Rican mothers and daughters communication on sex-related topics, and HPV, including the HPV vaccine. Design Thirty participants, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
8
1
Order By: Relevance
“…Our HCPs indicated that many adolescent Latinas with DM and their families were resistant to talking about RH-related topics. This is consistent with previous studies that indicate that RH-related communication is difficult due to some young Latinas’ discomfort about discussing sexuality with their mothers [28], their desire to please parents [29], and their reluctance to be forthright about sexual activity [29]. Prior research involving HCPs stated that there is often an intergenerational and inter-acculturation conflict regarding RH-related services because of clashes between traditional versus Americanized ideas on accessing RH services [29].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our HCPs indicated that many adolescent Latinas with DM and their families were resistant to talking about RH-related topics. This is consistent with previous studies that indicate that RH-related communication is difficult due to some young Latinas’ discomfort about discussing sexuality with their mothers [28], their desire to please parents [29], and their reluctance to be forthright about sexual activity [29]. Prior research involving HCPs stated that there is often an intergenerational and inter-acculturation conflict regarding RH-related services because of clashes between traditional versus Americanized ideas on accessing RH services [29].…”
Section: Discussionsupporting
confidence: 93%
“…This may help parents to feel that their teens are not personally being targeted for current sexual activity. Prior studies indicate that the concept of virginity is especially important in Latino sexual values and beliefs, which may affect RH-related communication between the Latina adolescent and her partner(s) [30], as well as the Latina adolescent and her family [28,29,31]. Often, Latino adolescents believed that parents disapproved of their access to RH-related services because of the high value placed on virginity before marriage, the belief that RH-related services are for pregnant or promiscuous women only, and that RH-related conversations encourage sexual activity and promiscuity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, familismo led mothers in our study to strongly believe that their daughters should trust them and come to them for help related to birth control and even pregnancy. This finding is at odds with another study involving mothers of Puerto Rican origin, who did not express this notion (Colon-Lopez et al, 2017); however, the daughters in our study were younger, and our mothers were not of the same national origin. Hence, it is unclear whether age, country of origin differences, or a combination of both of these factors may be moderating this belief.…”
Section: Discussioncontrasting
confidence: 99%
“…Findings are mixed regarding the impact of marianismo on mother-daughter communication about sex. Colon-Lopez et al (2017) found that marianismo limited communication about sex between mothers and daughters in Puerto Rico. In contrast, Torres et al (2016) found that stronger marianismo beliefs predicted more communication with children about sexual health topics by mothers of Puerto Rican families in Boston.…”
Section: Introductionmentioning
confidence: 99%
“…Our result is similar to others studies about the lack of knowledge of the association between HPV vaccine and cancer prevention in this population, but in contrast about knowledge on the HPV vaccine dose schedule. 19,20 On the other hand, hesitation towards vaccination in relation to early age of administration and side effects was discussed. Lack of awareness and understanding of the new policy was commonly mentioned, with resistance to this policy for the imposition of the government to their parental decisions regarding their child health 21 Issues such as lack of communication between them and the schools regarding this new policy was also mentioned.…”
Section: Discussionmentioning
confidence: 99%